(untitled) (World Bulletin of Education and Learning, 2025)
This scholarly article is devoted to a systematic analysis of the theoretical, methodological, and practical foundations for developing the creative competencies of fine arts teachers in composing and depicting landscape compositions. The study examines the specific characteristics of the landscape genre, compositional principles, color theory, and perspective, as well as the integration of these elements with pedagogical approaches from a scientific and educational perspective. The article substantiates the necessity of continuously improving the artistic and creative mastery of teachers and provides a scientific rationale for the role of independent creative exploration, particularly plein air practice, in the formation of professional competencies among both teachers and students.